Extracellular Vesicle-Mediated Immune Regulation of Tissue Remodeling and Angiogenesis After Myocardial Infarction - Sánchez-Alonso, Santiago; Alcaraz-Serna, Ana; Sánchez-Madrid, Francisco; Alfranca, Arantzazu (Frontiers in Immunology, 2018)
Myocardial ischemia-related disorders constitute a major health problem, being a leading cause of death in the world. Upon ischemia, tissue remodeling processes come into play, comprising a series of inter-dependent stages, including inflammation, cell proliferation and repair. Neovessel formation during late phases of remodeling provides oxygen supply, together with cellular and soluble components necessary for an efficient myocardial reconstruction. Immune system plays a central role in processes aimed at repairing ischemic myocardium, mainly in inflammatory and angiogenesis phases. In addition to cellular components and soluble mediators as chemokines and cytokines, the immune system acts in a paracrine fashion through exosome release. These vesicular structures participate in multiple biological processes, and transmit information through bioactive cargoes from one cell to another. Cell therapy has been employed in an attempt to improve the outcome of these patients, through the promotion of tissue regeneration and angiogenesis. However, clinical trials have shown variable results, which put into question the actual applicability of cell-based therapies. Paracrine factors secreted by engrafted cells partially mediate tissue repair, and this knowledge has led to the hypothesis that exosomes may become a useful tool for cell-free myocardial infarction therapy. Current exosome engineering strategies allow delivery of specific content to selected cell types, thus revealing the singular properties of exosomes for myocardial ischemia treatment.